A lightweight message authentication scheme for Smart Grid communications in power sector. (May 2016) - Mahmood, Khalid; Ashraf Chaudhry, Shehzad; Naqvi, Husnain; Shon, Taeshik; Farooq Ahmad, Hafiz
Highlights: Designed an authentication scheme for IoT based smart grid communication. Analyzed the scheme using automated tool ProVerif. The proposed scheme is more lightweight and secure than existing schemes. Abstract: The Internet of Things (IoT) has plenty of applications including Smart Grid (SG). IoT enables smooth and efficient utilization of SG. It is assumed as the prevalent illustration of IoT at the moment. IP-based communication technologies are used for setting SG communication network, but they are challenged by huge volume of delay sensitive data and control information between consumers and utility providers. It is also challenged by numerous security attacks due to resource constraints in smart meters. Sundry schemes proposed for addressing these problems are inappropriate due to high communication, computation overhead and latency. In this paper, we propose a hybrid Diffie–Hellman based lightweight authentication scheme using AES and RSA for session key generation. To ensure message integrity, the advantages of hash based message authentication code are exploited. The scheme provides mutual authentication, thwarting replay and man-in-the-middle attacks and achieves message integrity, while reducing overall communication and computation overheads.